Secondhand tobacco smoke exposure among children under 5 years old: questionnaires versus cotinine biomarkers: a cohort study - Joseph M Braun; Kimberly Yolton; Mónica Pérez-Ríos; Bruce Lanphear; Nerea Mourino; Maria Isolina Santiago-Pérez (BMJ Open)
Objectives Cotinine is the gold standard to estimate prevalence of secondhand tobacco smoke (SHS) exposure, and assay limit of detection (LOD) cut-points are typically used regardless of age. Our aim was to compare the concordance between mother-reported SHS exposure and serum cotinine categorising children as exposed with the assay LOD or age-specific cut-points.Design Data from the Health Outcomes and Measures of the Environment (HOME) Study, a prospective pregnancy and birth cohort.Setting Hospital or participants’ homes.Participants 389 pregnant women aged 18 years and older, between 13 and 19 weeks of gestation, living in a five-county region of the Cincinnati, Ohio metropolitan area, and with follow-up on their children at birth and ages 12, 24, 36 and 48 months.Primary and secondary outcome measures Children’s serum cotinine, mother-reported active smoking and SHS exposure were available at birth and during follow-up visits. We used Cohen’s kappa index to assess concordance between maternal self-report and child’s serum cotinine concentrations. We estimated optimal age-specific cut-points, their sensitivity–specificity and positive–negative predictive values with receiver operating characteristic curves.Results Self-reported exposure and cotinine data were available for 280 women who gave birth to singleton child. When applying the assay LOD (0.015 ng/mL), concordance between maternal report and serum cotinine, without accounting for age, was below 0.23 at all times. When using age-specific cut-points (12 months: 0.11 ng/mL; 24 months: 0.08 ng/mL; 36 months: 0.05 ng/mL and 48 months: 0.04 ng/mL), concordance improved, being low at 12 months (0.39), moderate at 24 and 36 months (0.47 and 0.43) and high at 48 months (0.62).Conclusions Concordance between mother-reported SHS exposure among children under 5 years and serum cotinine improved considerably after applying the cohort-specific and age-specific cut-points. Future studies are necessary to verify these results.